Rituximab rescue therapy for autoimmune pulmonary alveolar proteinosis. (2022) - Bird, Daniel; Evans, Jack; Pahoff, Carl
Abstract: Autoimmune pulmonary alveolar proteinosis (aPAP) is a rare lung disease characterised by abnormal alveolar surfactant accumulation due to macrophage dysfunction. Whole lung lavage (WLL) is the cornerstone of first-line aPAP therapy, but effective rescue treatments have not yet been well established. We report a case of a 41-year-old man with aPAP in whom further WLL is contraindicated. His diagnosis was established using a combination of classical radiological findings, positive serum GM-CSF IgG antibodies and bronchoalveolar lavage (BAL) findings. Following a literature review of emerging therapies, a decision was made to treat with a course of rituximab to suppress GM-CSF autoantibody production and restore alveolar surfactant-macrophage homeostasis. A significant clinical response was demonstrated within 6 months with improvements in arterial oxygenation, respiratory membrane gas diffusion, six-minute walk test and radiological findings.